2017
DOI: 10.1007/s10549-017-4158-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist and organizational factors associated with variation in breast cancer multigene testing

Abstract: Purpose Multigene testing for breast cancer recurrence risk became available in 2007, yet many eligible patients remain untested. This study evaluated variation in testing rates, and oncologist and organizational factors associated with variation, in a setting without financial influences on testing. Methods We conducted a retrospective cohort study using electronic data and oncologist surveys within Kaiser Permanente Northern California, a large integrated health care system. Analyses included all 2,974 tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In a qualitative study, local practice patterns and peer use of the test were found to influence clinicians' adoption of the assay. 23 Similarly, a recent Kaiser Permanente study found that differences in oncologist factors (eg, sex) and organizational factors (eg, use patterns among practice leaders) explained more variation in testing rates than patientlevel characteristics, 24 and another study (conducted in a single state) found that the likelihood of testing decreased for women when a clinician's patient volume decreased. 25 Thus, clinician-and organizationallevel factors may partially explain geographic variation in test uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, local practice patterns and peer use of the test were found to influence clinicians' adoption of the assay. 23 Similarly, a recent Kaiser Permanente study found that differences in oncologist factors (eg, sex) and organizational factors (eg, use patterns among practice leaders) explained more variation in testing rates than patientlevel characteristics, 24 and another study (conducted in a single state) found that the likelihood of testing decreased for women when a clinician's patient volume decreased. 25 Thus, clinician-and organizationallevel factors may partially explain geographic variation in test uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The observed rate of test receipt in KPNC is similar to or higher than that in most other settings. [13] Fourth, our results are limited to two large geographic regions in the Western United States. The respondents in this study were more likely to be white and more highly educated than women with breast cancer nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…The current report uses data from a larger multi-site, collaborative National Cancer Institute-funded study of GEP. [1315] All participating site Institutional Review Boards approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Geisinger Health System and Kaiser Permanente as examples, Reinke 27 identifies the need for leadership to encourage medical practitioners to make the move from genetics to genomics, noting that without this engagement, implementation will not succeed. Furthermore, Lieu et al 28 reported oncologists' genomic practices were influenced by leadership, placing this variable even ahead of funding, and argued for the need to leverage this to facilitate implementation.…”
Section: Leadershipmentioning
confidence: 99%